Evaluation of weight‐based prescription of antiretroviral therapy in children. Issue 3 (11th January 2019) - Dakshina, S; Olaru, ID; Khan, P; Raman, L; McHugh, G; Bwakura–Dangarembizi, M; Nathoo, K; Munyati, S; Mujuru, H; Ferrand, RA
Abstract : Objectives: The aim of the study was to investigate the extent of and factors associated with incorrect dosing of antiretroviral therapy (ART) in HIV‐infected children in Harare, Zimbabwe. Methods: All children aged 0–10 years and children aged 11–17 years who weighed < 35 kg and taking ART were recruited from the paediatric HIV clinic at Harare Hospital. Their current doses of ART drugs were compared against doses recommended by the national guidelines. Results: Among 309 children recruited [55% male; median age 7 years (interquartile range (IQR) 5–10 years)], the median CD4 count was 899 cells/μL and the median duration of their current ART regimen was 11.2 months (IQR 4.9–17.1 months). Overall, 110 (35.6%) children were prescribed incorrect doses of at least one drug component within their ART regimen; 64 (20.7%) under‐dosed and 49 (15.9%) over‐dosed on at least one drug. Children receiving a higher than recommended dose of at least one drug were younger compared with correctly dosed children (median 6 versus 7 years, respectively; P  = 0.001), had been on their current ART regimen for a shorter time (median 7.2 versus 13 months, respectively; P  = 0.003) and were less likely to be receiving a three‐drug fixed‐dose combination (FDC; 42.9 versus 63.3%, respectively; P  = 0.009). Those who were under‐dosed were also less likely to be on a three‐drug FDC (25 versus 63.3%, respectively; P  < 0.001). Conclusions: Over a third of children were prescribed incorrect doses of ART. Children taking triple‐drug FDCs were likely to be correctly dosed. Our study highlights the importance of weight monitoring at each clinical contact, training of health care providers on paediatric drug dosing and the need for wider availability of FDCs for children.